Advance and achievements of the methodology in science and technique of the Cuban Health System - Yordan Marrero Montoya; Alejandro López Rondon; Rachel de los Milagros Torres Mendoza; Aracelis Montoya Vázquez (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: the evaluation of the impact of the science and the technology constitutes a strategic necessity, as road of verification of the development of a country and of its scientific politics. Objective: to describe the methodology of the science and the technology, their achievements and advances in the Cuban national system of health. Method: it was taken to end like part of a work developed by the students in the development of the primary attention of health. It was gathered in the period of December to January of the 2020. They were not kept in mind exclusion approaches and they used scientific methods as: historical-logical; inductive-deductive and analysis-synthesis. Results: it was deepened in the behavior of the science and the technology in the last decades, being evaluated the achievements and advances of these in the Cuban system of health. The science and the technique have transcended for evolutionary stages that are guided in uncertainties among the environmental thing, the human thing, the education, and the social problems in front of the challenge of the sustainable development. Conclusions: from the implementation of the national system of science, technology and innovation, impelled by Fidel Castro Ruz, advances and important impacts have been achieved in the Cuban system of health among those that are: investigation centers, wide base technique of the system of health, to computerizeof the National System of Health, the automation.